2012
DOI: 10.1039/c2cc35208g
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative detection of single DNA molecules on DNA tetrahedron decorated substrates

Abstract: A single DNA molecule detection method on DNA tetrahedron decorated substrates has been developed. DNA tetrahedra were introduced onto substrates for both preventing nonspecific adsorption and sensitive recognition of single DNA molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 26 publications
(26 reference statements)
2
32
0
Order By: Relevance
“…To evaluate whether these DNA strands could be assembled into one complex, electrophoresis was conducted. As shown in Figure 2A, the four single strands could indeed assemble into the structure of DNA Td as previously described [29]. Moreover, the Apt-tail coupled with the Td and formed a larger DNA structure, indicating that Apt-Td could be constructed following our method.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…To evaluate whether these DNA strands could be assembled into one complex, electrophoresis was conducted. As shown in Figure 2A, the four single strands could indeed assemble into the structure of DNA Td as previously described [29]. Moreover, the Apt-tail coupled with the Td and formed a larger DNA structure, indicating that Apt-Td could be constructed following our method.…”
Section: Resultssupporting
confidence: 66%
“…Previous work by Wang et al has clearly demonstrated that the four DNA strands involved in this study can self-assemble into a DNA tetrahedron [29]. Here in this study, the original MUC1 aptamer was extended with an extra tail (Apt-tail) to serve as a sticky end.…”
Section: Resultsmentioning
confidence: 93%
“…In yet another approach, electrostatic interactions have been used to encapsulate QDs within a DNA nanocage by Wang et al, to conserve the single molecule aggregation-free state of QDs in solutions [99]. In a similar approach by Wang et al, QD-DNA conjugates have been used for the detection of a correctly 'folded' 3D DNA origami cage [100]. These conjugates are not only novel materials for design and assembly, but also display interesting electronic and chemical properties and therefore are valuable for understanding the macromolecular behaviour of complex nanomaterials.…”
Section: Synthetic Programmable Scaffoldsmentioning
confidence: 99%
“…Glass‐based fluorescence strategy is often used for quantitative analysis. In one study, DNA tetrahedron with amino groups could be anchored onto a glass slide via epoxy‐amino reaction . Through target‐induced streptavidin‐biotin binding, quantum dots (QDs) were captured as fluorescent probes on DNA nanostructures.…”
Section: Fna‐based Biosensorsmentioning
confidence: 99%